(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The article identifies the importance of security management of foreign economic activity, analyzes in detail the approaches of various authors to the choice of performance indicators of foreign economic activity of the enterprise. Scientists offer calculations of absolute and relative indicators to characterize export-import operations. We have selected indicators that, in our opinion, best determine the effectiveness of security management of foreign economic activity. The article proposes a method of assessing the security management of foreign economic activity of the enterprise. To determine the level of security management of foreign economic activity of the enterprise should take into account the following indicators: export efficiency ratio, import efficiency ratio, overdue liabilities ratio, the share of exports in total sales, profitability of export sales, the share of profits from exports in total profit of the exporting enterprise, the share of products certified for compliance with international standards, the level of competitiveness of the exporter. The paper selects indicators to assess the level of security management of foreign economic activity. Limit values and specific weight of the listed indicators with the use of expert method and generally accepted threshold values are determined. Taking into account the actual values of indicators that characterize the level of security of management of foreign economic activity, and the gradation of their levels, we convert the values of the criteria into points. The next step is to calculate the integrated indicator of the level of security management of foreign economic activity. Interpretation of the integrated indicator is carried out by quantitative and qualitative characteristics. The gradation and characteristics of the levels of security management of foreign economic activity of the enterprise are developed in the work. The proposed method is based on the analysis of existing methodological and individual approaches using an expert approach and takes into account the characteristics of enterprises in the engineering industry. The methodology will allow to determine strategic guidelines for the development of measures to prevent and eliminate threats in the implementation of foreign economic activity. We used the proposed method to assess the level of security management of foreign economic activity of the SKF Ukraine.